Hereditary Deficiency of Blood Coagulation Factor I - Afibrinogenemia, Clinical Observation Medical Center of Hematology of the Ministry of Health of The Republic of Uzbekistan. - Juraeva Nodira Tukhtapulatovna; Mahmudova Aziza Dzhumanovna; Ismoilova Zulfiya Abdufattokhovna (Zien Journals, 2022)
Afibrinogenemia is a congenital hemorrhagic syndrome with an autosomal recessive mode of transmission, which occurs due to a lack of synthesis of factor I (fibrinogen) and is clinically characterized by the occurrence of large post-traumatic bleeding. It is characteristic of a patient with afibrinogenemia that his tendency to bleed is never spontaneous; it is always a consequence of some trauma (sometimes so minor that it can go unnoticed). The first manifestation of the disease occurs at the very moment of the birth of the patient, that is, when the umbilical cord is cut off; this surgical trauma causes severe hemorrhage with a very high mortality rate. The significant frequency of this early onset of afibrinogenemia (70-80% of cases), compared with such a low frequency in hemophilia (3-4%), is due to the fact that maternal antihemophilic globulin, which has a small molecule, passes through the placenta and protects the hemophilic fetus at birth; on the contrary, maternal fibrinogen, which has a large molecule, cannot pass through the placental barrier to protect the afibrinogenamic fetus. In addition, the umbilical cord is very rich in tissue thromboplastin, which can cause blood coagulation (externally) in a hemophilic fetus, but without any effect in the case of an afibrinogenemic fetus. The same hemorrhagic episode occurs on the occasion of circumcision, in male children of the Jewish or Moslem religion; here the frequency is the same as in hemophilia. Hemorrhagic episodes are more frequent during childhood, with its inevitable trauma, in the adult they are much thinner
Keywords: afibrinogenemia; rare hereditary coagulopathy; congenital fibrinogen deficiency; fibrinogen